Eksistensi Maccera Manurung dalam Perspektif Nilai Islam - Sitti Fatimah Dwi Putri (Rihlah : Jurnal Sejarah dan Kebudayaan, 2019)
Maccera Manurung is a La Pariba heritage heirloom washing ceremony, as well as an expression of gratitude for the people of Matakali for the abundance of fortune from Allah swt received for a year. Whether it's a fortune in the form of health and abundant harvests. The author uses a type of qualitative research with a descriptive analysis of the objects discussed according to the reality that occurs in the community, especially in the Matakali community, Maiwa District, Enrekang Regency. The emergence of an unknown human figure in Matakali Enrekang that is able to bring positive change in the Matakali region and is known as Tomanurung La Pariba. The Matakali community agreed to appoint La Manariung to manurung La Pariba as a leader in their area until birth and his child called To Jabbari and then La Pariba suddenly also disappeared by leaving several objects namely Kawelang, Tengkeng Bassi and rifles, and then the objects of La Pariba were disposed of by the Matakali people as Maccera Manurung who also commemorated the services of La Pariba. Maccera Manurung merupakan upacara pencucian benda pusaka peninggalan La Pariba, sekaligus ungkapan rasa syukur masyarakat Matakali atas limpahan rezki dari Allah swt yang diterima selama setahun. Baik itu rezki berupa kesehatan maupun hasil panen yang melimpah ruah. Penulis menggunakan jenis penelitian kualitatif dengan analisis deskriptif mengenai objek yang dibicarakan sesuai kenyataan yang terjadi di masyarakat, khususnya pada masyarakat Matakali Kecamatan Maiwa Kabupaten Enrekang. Kemunculan sosok manusia yang tidak diketahui asal-usulnya di Matakali Enrekang yang mampu membawa perubahan positif di wilayah Matakali dan dikenal dengan Tomanurung La Pariba.masyarakat Matakali sepakat mengangkat to manurung La Pariba sebagai pemimpin di wilayah mereka hingga saat lahir dan dewasa anaknya yang bernama To Jabbari dan kemudian La Pariba tiba-tiba pula menghilang dengan meninggalkan beberapa benda yaitu Kawelang, Tengkeng Bassi dan senapan yang kemudian benda-benda peninggalan La Pariba tersebut diupacarakan oleh masyarakat Matakali dengan sebutan Maccera Manurung yang juga untuk mengenang jasa-jasa La Pariba.